Evaluation of geographical aggregation of solar photovoltaic generation in Singapore - Xie, Chen (2017)
The capacity of photovoltaic generation in Singapore is rapidly increasing. Large and rapid changes in the output of PV plants are possible because of the intermittent and stochastic nature of solar PV. Such uncertain power fluctuations may cause many issues that threaten the secure and reliable operation of power system. One way to alleviate these issues is to deploy distributed PV generation in multiple different sites, as geographic diversity can significantly reduce the magnitude of extreme changes in aggregated PV output. This dissertation put forward several parameters which are used to evaluate the smoothing effect of the geographical distribution of the PV plants. Also some figures in the time and frequency domain is proposed. After the data analysis processing, the results of the different timescale and combination were compared. So at last the influence factor of the smoothing effect is given and discussed based on the result figures. As the dissertaion stated, the PV generation output surely can be improved by the geographical distribution, which will highly improve the quality and stability of the solar generation power. This has a large significance to the development of the solar energy.